Research of gas content and interfacial area in the downflow pipes of a circulation apparatus with jet injection gas filling - Ved, Viktor; Nikolsky, Valeriy; Okhtina, Oxsana; Kiselev, Vadym (Technology audit and production reserves, 2019)
The object of research is an apparatus with jet injection gas filling. The studies are conducted on an experimental installation of a working medium of water-air. The distribution of gas phase bubbles is studied depending on the operating parameters of the apparatus. The value of the local and total gas content, as well as the specific surface of the phase contact, is determined. The gas content and the contact surface of the phases in the downflow pipes of the circulation apparatus with jet injection gas filling are investigated. The use of circulating apparatuses with jet injection gas filling is promising for carrying out mass transfer and reaction mass transfer processes. Due to the use of water energy for gas filling of the reaction space, the devices have advantages over airlift and gas-lift devices, bubble columns in chemisorption processes with slightly soluble gases. Experimental studies of the gas content and the contact surfaces of the phases from the operating-technological and hardware-structural parameters makes it possible to determine the optimal operating conditions. According to the results of studies, it is found that the diameter of the bubbles increases with an increase in the number of revolutions of the shaft of the mixing device. The mode of suspension of the gas phase took place at shaft rotation numbers from 600 rpm up to 750 rpm. With an increase in the number of revolutions, the resistance to the force of bubbling of bubbles increases and the suspension mode switches to the gas-liquid flow circulation mode. The ability to control the gas saturation process due to fluid circulation, regardless of the fluid load of the apparatus, is one of the advantages of the developed design. It is established that the total gas content in the downflow channels varies from 0.07–0.10 to 0.1–0.18, which is typical for gas-liquid devices. The total gas content in the downflow channels of the apparatus is in the range from 100 to 260 m2/m3 of the reaction volume and is typical for most gas-liquid bubblers. The results of studies of the operating modes of the apparatus with jet injection gas filling in the suspension mode of the gas phase can be used to calculate the mass transfer coefficient.